Arabs in the Future: Techno-Orientalism in Dune Film - Medellel, Ouissal; Bouhelal, Zannoubia Nour El houda (University of Eloued جامعة الوادي, 2024)
تعود جذور التمثيل الغربي للشرق إلى الحركة الفنية للاستشراق، حيث استمر هذا التمثيل تاريخيا في تكريس الصورة النمطية و الانتقاص الثقافي، خصوصا عندما يتعلق الأمر بالعرب. إلا أن ظهور "الاستشراق التكنولوجي" أضفى طابعا جديدا و معاصرا للتصور الغربي للشرق الأقصى الذي أصبح يُصَوَّر على أنه متقدم تكنولوجيا و متخلف ثقافيًا في نفس الوقت. و على الرغم من التقدم التكنولوجي أيضا في الدول العربية إلا أنه يتم تجاهله. تعالج هذه الدراسة التأثير المستمر للعدسة الاستشراقية في تشكيل صورة العرب حتى في البيئات المستقبلية كأفلام الخيال العلمي. يسلط هذا البحث الضوء على "كُثَيْب" و هو احد أفلام الخيال العلمي الغربي و الذي تدور أحداثه في كون بعيد يوازي الشرق الأوسط. يناقش هذا البحث العلاقة بين "الاستشراق التكنولوجي" و صورة العرب في المستقبل. من خلال مراجعة شاملة للمراجع السابقة و تحليل محتوى نوعي شامل للفيلم ، تظهر هذه الدراسة استمرارية المنظور الاستشراقي في تصوير العرب في فيلم كثيب (2021) بالرغم من البيئة المستقبلية التي تدور فيها أحداث الفيلم. Tracing its roots to the aesthetic movement of Orientalism, the Western representation of the Orient has historically perpetuated stereotypes and cultural reductions, particularly in relation to Arabs. Despite the recent and speedy technological advancements in Arab countries, the emergence of techno-Orientalism presents a contemporary lens through which the Far East is depicted as simultaneously intelligent and culturally backward while the Near East, “particularly Arabs,” seem to be left out. This research delves into the persisting influence of Orientalist views in shaping perceptions of Arabs, even within the futuristic settings portrayed in Western science fiction. Using the science-fiction film Dune as a case study, which envisions a distant universe with a parallel to the Middle East, this study examines the concept of techno-Orientalism and how it correlates to the portrayal of Futuristic Arabs. The research seeks aims to unveil the nuances of the representation of Arabs and critically contribute to the discourse on cultural perception of Arabs in the age of technological evolution. Through a thorough review of relevant literature, and a qualitative content analysis that is adapted to provide a comprehensive analysis of the film, this study shows the persistence of Orientalist perspectives in the portrayal of Arabs in Dune (2021), despite the film's futuristic setting.
Literature and Civilization
Keywords: العرب، كثيب، الاستشراق، الاستشراق التكنولوجي، أفلام الخيال العلمي; Arabs; Dune; Orientalism; Techno-Orientalism; Sci-fi films